Some microwave properties of yttrium iron garnet and magnetite filled thermoplastic natural rubber composites / Junaidah M. S …[et al.] - M. S, Junaidah; H. A, Mustaffa; H. A, Sahrim; H.Y, Ahmad Nazlim; A, Nazree (2004)
A thermoplastic natural rubber (TPNR) was prepared by melt-blending of polypropylene (PP), natural rubber (NR) and liquid natural rubber (LNR) in a weight ratio of 70:20:10 using a standard method. LNR as the compatibiliser was prepared earlier by photodegradation of NR in visible light. Samples of TPNR filled with different mixtures of YIG and magnetite powders were then prepared using the same method with a fixed TPNR content of 70% of the total weight. The effects of incorporating different composition of YIG and magnetite into the matrix of TPNR on the microwave properties were studied. The complex scattering parameters (S11*, S21*, S12* and S22*), microwave dielectric permittivity (ƹr* = ƹ r - jƹ), magnetic permeability (µr* = µr”) and absorption properties of the samples were measured using a microwave vector network analyzer (MYNA) by means of coaxial two-port and single-port techniques in the frequency range of 0.3 - 13.5 GHz. The change in YIG and magnetite composition influences the values of the reflected (Pr), transmitted (Pt) and absorbed (PR) power. The reflection loss, RL is calculated from ƹr* and µr* using a metal-backed absorber model. RL is found to depend on the thickness of the absorber. Two dips are found at low and high frequency regions for all the samples, which occur at the thickness of the material eq1Jal to AJ4 daJ1 3A/4 respectively, where A is the propagation wavelength in the materials. The measured RL curve from the single-port technique is in accordance with theoretical calculations. RL under a transverse external magnetic field of 1 T decreases and the matching frequency shifts forward. The incorporation of different type and percentage of the ferrite into the matrix of TPNR has resulted in significant differences in the microwave properties of the composites. These composites can be used as an electromagnetic wave absorber based on a selective frequency band for samples with suitable thickness.